Learning reflective practice: an autoethnographic performance in six movements - Grellier, Jane Isobel (Curtin University, 2015)
This work is an autoethnographic performance of first-year teaching and learning at Curtin University in Western Australia in the years 2008–2014. I integrate traditional ethnographic and academic voices with narrative, poetry, composite choruses and voices of students and teachers. I also create a provocateur character, who problematises the institution and challenges easy responses to tertiary education. I seek to encourage the reader to join me in reflecting on learning and on managerialism in universities.